AIR QUALITY MONITORING IN INDUSTRIAL ESTATE (Case Study: Jababeka Industrial Estate, Cikarang) - Filson Maratur Sidjabat; Rijal Hakiki; Temmy Wikaningrum (President University, 2019)
Ambient Air Quality Monitoring (AAQM) must be conducted by Industrial Estate Management, according to legislation and regulation in EIA (Environmental Impact Assessment) Report. AAQ test parameter are Sulfur Dioxide (SO2), Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Ozon (O3), Hidrocarbon (HC), PM10, PM2,5, Total Suspended Solid (TSP), and Lead (Pb). Industrial Estate Management has an extensive role in AAQM, analysing and organizing better environmental policies. The data of Jababeka Industrial Estate (JIE) AAQM was seized from EIA Report each semester from year 2015 to 2018 and analyzed using openair model. A review of AAQM and Management in other industrial estate was done as a lesson-learned and insight to improve the AAQM System in JIE. Openair model can analyze the AAQ data with meteorological data around the sampling point area, and visualize it through the pollution rose function. The limited data of AAQM and weather, will limitate the result and analysis. The future research must aims to make a real-time/continuous AAQM and meteorological data to get more accurate and comprehensive data modeling and analysis.